Career Success Model: A Case Study of Information Technology Graduates - Julianti Kasih; Doro Edi; Radiant Victor Imbar (Jurnal Teknik Informatika dan Sistem Informasi, 2021)
Success in a career is everyone's dream, and it is not an exception for Information Technology graduates who are engaged in information technology-related jobs. Several studies have documented the role of the following two (2) constructs, namely Career Competence (CC) and Lecturer Competence (LC), in Career Success (CS). The authors believe that University Commitment (UC) must be included in this list. This research aims at developing a model that explains and measures the relationship amongst those four (4) constructs. The model that will be developed is based on the Structural Equations Modelling Technique. Respondents participating in this research are IT graduates working in IT-related jobs who have graduated from three (3) private universities in Bandung (Indonesia), namely, Maranatha Christian University (UKM), Parahyangan Catholic University (UNPAR), and Harapan Bangsa Institute of Technology (ITHB)) with graduating years ranging from 2006 to 2018. The collected data will be processed using IBM SPSS AMOS. This research proves that firstly, LC influences both UC and CC, secondly, UC influences CC, and lastly, CC affects CS. Further hope this model can be developed for other universities in Indonesia to increase Lecture Competency and University Commitments by the strategic plans of each university. Respondents participating in this research are IT graduates working in IT-related jobs who have graduated from three (3) private universities in Bandung (Indonesia), namely, Maranatha Christian University (UKM), Parahyangan Catholic University (UNPAR), and Harapan Bangsa Institute of Technology (ITHB)) with graduating years range from 2006 to 2018. The collected data will be processed using IBM SPSS AMOS. This research proves that firstly, LC influences both UC and CC, secondly, UC influences CC, and lastly, CC affects CS. Further hope this model can be developed for other universities in Indonesia to increase Lecture Competency and University Commitments by the strategic plans of each university. Keywords— Department of Information Technology, Career Success, Commitment of Higher Education Lecturer Competency, Career Competence